2022
DOI: 10.2147/dddt.s335024
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin Attenuates High Glucose-Induced BMSC Dysfunction via the Activation of the PI3K/AKT/Nrf2 Signaling Pathway

Abstract: Purpose: High glucose environment in diabetes mellitus induces the dysfunction of bone marrow-derived mesenchymal stromal cells (BMSCs) and impairs bone regeneration. Chrysin is a natural polyphenol with outstanding anti-inflammation and anti-oxidation ability. However, whether and how chrysin affects BMSCs in high glucose conditions remain poorly understood. The present study aimed to explore the effects and underlying mechanisms of chrysin on the BMSCs exposed to high glucose environment. Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…an adverse effect on bone quality. In vitro experiments have proven that high glucose environment exerts an inhibitory action on the osteogenic differentiation and growth of osteoblasts and bone marrow stroma cells (BMSCs) (18,56). Glycolysis is a fundamental metabolic pathway for glucose catabolism.…”
Section: High Glucose Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…an adverse effect on bone quality. In vitro experiments have proven that high glucose environment exerts an inhibitory action on the osteogenic differentiation and growth of osteoblasts and bone marrow stroma cells (BMSCs) (18,56). Glycolysis is a fundamental metabolic pathway for glucose catabolism.…”
Section: High Glucose Environmentmentioning
confidence: 99%
“…Furthermore, there is also study showing that sustained hyperglycemia may trigger cellular innate immune responses, activate reactive oxygen species (ROS)-producing enzymes localized on the outer mitochondrion, resulting in overproduction of ROS and cell dysfunction (59). Therefore, in recent years, a large number of studies have focused on how to rescue the impaired osteogenesis differentiation ability of BMSCs and osteoblasts (56,57,60,61). That is very critical and meaningful way to find novel therapeutic targets for diabetic osteoporosis.…”
Section: High Glucose Environmentmentioning
confidence: 99%
“…A more beneficial way would be activating innate pathways that promote endogenous antioxidants production in vivo, such as the nuclear factor erythroid 2-related factor 2 (NRF2) pathway [ 194 , 195 ]. Chrysin is reported to promote bone regeneration in type 1 diabetic rats and protect BMSCs from high glucose-induced oxidative stress by PI3K/AKT/Nrf2 pathway [ 196 ]. Nevertheless, as older people have a higher risk of cancer development, another significant concern may be raised because of the potential effect of antioxidants on cancer promotion.…”
Section: Therapeutic Approaches To Rejuvenate Aged Mscsmentioning
confidence: 99%
“…According to the literature reports, the most reliable pharmacological activities of chrysin are antioxidant, anti-inflammatory, anti-diabetic, hepatoprotective, neuroprotective, anti-aging, and anticancer effects [ 213 – 215 ]. In many studies, it has been reported that chrysin occupies an axial role in many biological process for example suppression the pro-inflammatory cytokines expression, down-regulation of nuclear factor kappa B (NF-kB), tumor necrosis factor α (TNF-α), and interleukin 1β (IL-1β), up-regulation of apoptotic pathways, and inhibition of angiogenesis and metastasis formation [ 216 218 ]. Gao and colleagues have been reported a higher level of Nrf2 expression in BEL-7402/ADM cells.…”
Section: Nrf2 Inhibitorsmentioning
confidence: 99%